Kajian Kodikologi Iluminasi dalam Serat Jaya Lengkara Wulang (1803) - Mayasari, Devita Herda Ayu (Arnawa, 2023)
This study aims to identify and analyze the symbols in the illumination of the Jaya Lengkara Wulang manuscript. This codicological study uses a qualitative descriptive method. This qualitative descriptive is used to explain the symbols in the illumination. The source of the research data is the illumination of the Renggan Jaya Lengkara Wulang district head, a collection of the British Library. The results showed that there were elements of pineapple, praba, sunflower, saton, daisies/asters, tlacapan, lung-lungan, and arrow motifs. In addition, there are also elements of color, namely gold, red, blue, yellow, and white. If it is related to the contents of the text, there are teachings to have broad insight, be firm in your stance, have good manners, and always be compassionate towards others. === Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis simbol-simbol dalam iluminasi naskah Jaya Lengkara Wulang. Penelitian kodikologi ini menggunakan metode deskriptif kualitatif. Deskriptif kualitatif ini digunakan untuk menjelaskan simbol-simbol dalam iluminasi. Sumber data penelitian adalah iluminasi wedana renggan Jaya Lengkara Wulang koleksi British Library. Hasil penelitian menunjukkan adanya unsur motif buah nanas, praba, bunga matahari, saton, bunga daisy/aster, tlacapan, lung-lungan, dan anak panah. Selain itu juga ada unsur warna, yaitu emas, merah, biru, kuning, dan putih. Jika dikaitkan dengan isi teks terdapat ajaran untuk berwawasan luas, teguh pendirian, memiliki tata krama, dan selalu berbelas kasih kepada sesama.